Evaluation of arobiological characteristics of persimmon varieties - Nazarov Abduqodir; Nazarov Abduqahhor; Khakimova Malokhat; Khakimova Mavjuda (BIO Web of Conferences)
In this scientific article, the persimmon palm is a subtropical plant of which there are many species. More than 800 varieties of persimmons have been studied and propagated around the world. Such varieties and forms are effective as large-fruited, fertile, seed-bearing and pollinating trees with flowering at the same time. Today, the drying of persimmon fruits in the world is common in China, Japan, Korea and Brazil. Ripe, but not yet softened hard fruits are peeled off and hung on a string.